1993
DOI: 10.1113/jphysiol.1993.sp019825
|View full text |Cite
|
Sign up to set email alerts
|

Synapse formation and elimination during growth of the pectoral muscle in Xenopus laevis.

Abstract: SUMMARY1. Synapse formation and synapse elimination were studied in the pectoral muscle of Xenopus laevis.2. Histology showed that fibres were not added during postmetamorphic growth. Most fibres were innervated at two widely separated junctions and this number did not change as frogs grew.3. Intracellular recording revealed that fibres with two junctions could be mononeuronally innervated, or innervated in one of three different polyneuronal patterns. A growth-related shift in innervation pattern was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…Although the overall proportion of fibers showing innervation of both end plates by the same axon with or without inputs from other axons ( a _ / a-) was very high (82.3%), the fraction showing pure DMI ( a / a , 57%) was significantly lower than reported from earlier experiments (66% in Nudell and Gnnnell, 1985; 92% in large adults in Dunia and Herrera, 1993 ). Many inputs in the present experiment were less than 1 mV in amplitude and would not have been detected had curare or other postsynaptic blocking agents been used to reduce EPPs below the threshold.…”
Section: Dmicontrasting
confidence: 69%
See 2 more Smart Citations
“…Although the overall proportion of fibers showing innervation of both end plates by the same axon with or without inputs from other axons ( a _ / a-) was very high (82.3%), the fraction showing pure DMI ( a / a , 57%) was significantly lower than reported from earlier experiments (66% in Nudell and Gnnnell, 1985; 92% in large adults in Dunia and Herrera, 1993 ). Many inputs in the present experiment were less than 1 mV in amplitude and would not have been detected had curare or other postsynaptic blocking agents been used to reduce EPPs below the threshold.…”
Section: Dmicontrasting
confidence: 69%
“…This suggests some fiber addition with growth, but we do not consider this a significant change because the fibers were much smaller in the smaller individuals and some fibers may have been missed. Dunia and Herrera ( 1993) found no addition of fibers, based on fiber counts in the procoracoid region of the muscle in small and large Xenopus. Haimann et al ( 1981a) reported that the anterior and posterior nerves contained approximately 19 and 35 motor axons, respectively, in nerves that had their spinal ganglia destroyed, removing the sensory component.…”
Section: Mature Innervation Patternmentioning
confidence: 98%
See 1 more Smart Citation
“…Cases of apparent synapse elimination and formation of new polyneuronal innervation have been directly observed in frogs (Herrera and Werle, 1990;Herrera et al, 1991). In addition, synapse replacement, wherein the innervation provided by one nerve terminal is substituted by innervation from another terminal, seems to be common in the pectoralis muscle (supracoracoideus) of Xenopus laevis, in which it can be strongly inferred from physiological measurements (Dunia and Herrera, 1993).…”
Section: Abstract: Reinnervation; Synaptic Plasticity; Synaptic Remomentioning
confidence: 86%
“…The developmental progression of the trigeminal motor system is in stark contrast to other amphibian systems that have been presented as models of neuromuscular ontogenesis [Letinsky and Morrison-Graham, 1980;Morrison-Graham, 1983;Bennett et al, 1985;Jans et al, 1986;Herrera et al, 1990;Dunia and Herrera, 1993]. Most of these have focused on limb muscles, such as the sartorius and cutaneous pectoris, which show a more typical pattern of neuromuscular maturation.…”
Section: Discussionmentioning
confidence: 99%